Blood Lost: A Retrospective Review of Blood Wastage from a Massive Transfusion Protocol in a Tertiary Paediatric Hospital - Debbra Chong; Joyce Ching Mei Lam; Xun Yi Jasmine Feng; Mui Ling Heng; Yee Hui Mok; Li-Wei Chiang; Kee Chong Ng; Yong-Kwang Gene Ong (MDPI AG, 2022)
Background: The paediatric massive transfusion protocol (MTP) is activated in the paediatric population for both trauma and non-trauma related indications. While it helps to improve the efficiency and efficacy of the delivery of blood products, it can also result in increased wastage. We aimed to evaluate the wastage rates from our paediatric MTP activations from 2013 to 2018. Method: As part of an audit, we retrospectively reviewed the records of the paediatric patients who had MTP activations. We collected the following data: reason for MTP activation, weight of patient, number of cycles of MTP required, blood products used, blood products wasted, deviation from our institution's recommended MTP blood product ratio, and reason for wastage. Result: We had 26 paediatric MTP activations within the audit period. There was an overall wastage rate of 1.5%, with wastage occurring in 3 out of 26 patients. The reason for all wastage was demise of the patient. Most patients' transfusion ratios deviated from our institution's MTP protocol. Conclusion: Our wastage rates are low likely because of clear MTP activation guidelines and a flexible MTP workflow.